Mortality Assessment of Pediatric Septic Patients Through Pediatric Sofa+Anion Gap and Pelod-2 Scores - Siampa, Johaan Pawe; Utariani, Arie; Hanindito, Elizeus (Folia Medica Indonesiana, 2022)
Highlight: • Sepsis and septic shock cause morbidity and mortality in pediatric patients. • The accuracy of pediatric sequential organ failure assessment and anion gap (pSOFA+AG) was compared with AG and pediatric logistic organ dysfunction-2 (AG+PELOD-2). • The mortality assessment of pediatric septic patients showed that pSOFA was more sensitive than PELOD-2, while pSOFA+AG was not more sensitive than PELOD-2. Abstract: Sepsis and septic shock are some of the causes of morbidity and mortality (50-60%) in pediatric patients treated in intensive care rooms. This study aimed to compare the accuracy of pediatric Sequential Organ Failure Assessment (pSOFA) score combined with anion gap (AG) score to Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score in the assessment of mortality in pediatric septic patients at the Resuscitation Room of Dr. Soetomo Geeneral Academic Hospital, Surabaya, Indonesia. This was a retrospective observational cohort study using pediatric sepsis diagnosis guidelines based on the 2016 Pediatric Sepsis Consensus and medical records between January-December 2018. All data of patients aged 1 month to 16 years with suspected infection at the Resuscitation Room were collected based on predisposing infections, signs of infection, and warning signs. Organ dysfunction was assessed by calculating the pSOFA+AG scores, PELOD-2 scores, and corrected anion gap (cAG) in the first 24 hours. Sepsis mortality was assessed by comparing the results of the pSOFA, pSOFA+AG, and PELOD-2. The results showed 94.9% sensitivity and 70.0% specificity (p<0.0001) in the pSOFA, 89.9% sensitivity and 71.3% specificity (p<0.0001) in the PELOD-2, 79.7% sensitivity and 65% specificity (p<0.0001) in the AG, 79.7% sensitivity and 73.8% specificity (p<0.0001) in the cAG, and 79.3% sensitivity (p<0.0001) in the pSOFA+AG. In conclusion, pSOFA was more sensitive than PELOD-2, while the use of pSOFA+AG was not more sensitive than PELOD-2 in assessing the mortality of pediatric septic patients.